Medicine Prescribing Pattern and Knowledge on Medicine Use at Different Level of Health Care Settings in Nepal - Gyanwali, Pradip; Dhakal, Neelam; Humagain, Baburam; Karki, Khem Bahadur (Journal of Nepal Health Research Council, 2020)
Background: It is imperative to have adequate knowledge about medicines being used for their proper administration so as to obtain desirable therapeutics effects. This study aims to assess the medicine prescribing pattern and patients’ knowledge about medicine use at different level of health care settings in Nepal. Methods: A cross sectional study was conducted in randomly selected 88 health facilities in Nepal. Altogether 2200 patients, taken randomly after the doctor visit, were interviewed and assessed for the prescription. Results: Out of total drugs prescribed from 88 health facilities (6,175), 68.91% were essential drugs, 23.74 % were antibiotics and 61 % of medicines were prescribed in generic names. And among patients receiving medicines, adequate response on medicine use was received on 49% of medicines out of 3,806 medicines dispensed. Conclusions: Greater percentages of medicines were prescribed from essential drug list in health facilities. Knowledge on medicine use was poor among people. Keywords: Antibiotics use; drug prescribing pattern; knowledge; rational use of drugs